Servant Leadership in Higher Education - Alicia Domack (Academic Chairpersons Conference Proceedings, 2019)
The purpose of this presentation is to orient the audience to the tenets of servant leadership and provide examples of how servant leadership can be applied in higher education.
Keywords: servant leadership; self awareness; listening; changing the pyramid; empathy; building community